Queering the Map: Stories of love, loss and (be)longing within a digital cartographic archive. (September 2021) - Kirby, Emma; Watson, Ash; Churchill, Brendan; Robards, Brady; LaRochelle, Lucas
The rise of crowdsourced and participatory digital platforms which aim to make visible the experiences of otherwise marginalised people are significant within the broader landscape of digitally mediated community spaces. One example of such media is Queering the Map, a digital storymapping platform where users anonymously pin 'queer moments' and memories to places. While the mediation of affect and intimacy in digital spaces among queer people is increasingly attended to in scholarly work, the cartographic and archival remains hitherto underexplored. Drawing on an analysis of almost 2000 micro-stories geolocated to Australia, in this article we explore various aspects of story contribution that situate Queering the Map as a lively cartographic archive. Rather than necessarily anonymous (as the platform dictates), the posts, we argue, entail various deliberated directions or gestures, encoded for audiences: what we term stories for someone . We highlight these publicly private stories' connective and affective underpinnings, and the political potentialities (and problems) therein for queer belonging and community-building. In doing so we seek to contribute to scholarship on digital archives, crowdsourcing, and advance conceptualisations of digital intimacies.